Safety analysis of hydraulic anti-kink system on S curve passing of tram - FAN Qingyu; CHI Maoru; LUO Yun; LI Yixiao; WANG Huansheng (机车电传动)
Based on the principle of hydraulic anti-kink system, a four-module single vehicle type tram model with traditional wheelsets and a simplified dynamic model of the anti-kink system was established for the bending phenomenon caused by the single-type tram passing through the curve. The force condition and the dynamic performance of tram passing through C-shaped circular curve and S-shaped curves with different intermediate straight line lengths were compared and analyzed under the action of anti-kink system. The results show that: 1) In terms of limits, the anti-kink system can make the head-shaking angle difference between the front and following car body and the bogie of the same module tend to be consistent on a small radius curve, effectively reducing the maximum head-shaking angle of the vehicle, and preventing the vehicle from bending on the curve. 2) In terms of dynamics, when passing the C-shaped circular curve and the S-shaped curve with a long intermediate straight line, the installation of the anti-kink system is conducive to the smooth entry of the rear vehicle into the curve, the wheel-rail lateral force and the derailment coefficient of the front guide wheel of the same module increase slightly, while the wheel-rail lateral force and the derailment coefficient of the following guide wheel guide decrease. When passing the S-shaped curve with a short intermediate straight line, the installation of the anti-kink system is not conducive to the curve passing, in the same module, the wheel-rail lateral force and the derailment coefficient of the front and the following guide wheel both increase. 3) It is not recommended to install hydraulic anti-kink system on the S-shaped curve when the length of the intermediate straight line is less than the fixed distance of the bogie; On the contrary, the tram may consider installing hydraulic anti-kink system.